The Constitutional Development of Slovenia (1918 – 2021) - Bardutzky, Samo (Comparative Constitutionalism in Central Europe: Analysis on Certain Central and Eastern European Countries, 2022)
The chapter deals with the constitutional development in Slovenia from the end of World War I to the present day, covering roughly a century. This is the period of time during which Slovenia went from belonging to the Habsburg monarchy to being a part of the inter-war monarchy of the South Slavs, experienced the trauma and devastation of World War II and then became a part of the Yugoslav federation. Thirty years ago, in 1991, it gained statehood and adopted a liberal constitution still in force today. The chapter discusses these periods and sees the different changes and upheavals as milestones that helped shaped Slovenian constitutional identity. It also presents an overview of the constitutional order under the 1991 Constitution and finally, discusses what the authors suggests are some of the elements of the constitutional identity of Slovenia.KEYWORDS: Slovenia, Kingdom of Yugoslavia, socialist Yugoslavia, federalism, statehood, democracy, human rights and fundamental freedoms, constitutional identity, gender equality, right to language, distrust towards the military, European constitutionalism.